1991
DOI: 10.1084/jem.173.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Preferential utilization of specific immunoglobulin heavy chain diversity and joining segments in adult human peripheral blood B lymphocytes.

Abstract: SummaryWe have examined at the molecular level the CDR3 and adjacent regions in peripheral blood B lymphocytes of normal individuals. A total of 111 sequences (12-28 sequences from six individuals) were obtained after cloning of the polymerase chain reaction-amplified segments into plasmids or phage . The average length of the VDJ joining was 109 nucleotides, with a range from 79 to 151 . Approximately 75% of the sequences were in frame when translated into amino acids . Among the JH segments, J H4 was found m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
182
3

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(222 citation statements)
references
References 19 publications
(17 reference statements)
37
182
3
Order By: Relevance
“…In contrast, an extraordinary diversity in length and composition of the CDR3 was described for a set of RA-derived polyreactive antibodies and RF [30] and rearranged V H genes from PBL of a healthy donor [17]. For the J H segments we can confirm a predominant use of J H 4 [17,19].…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, an extraordinary diversity in length and composition of the CDR3 was described for a set of RA-derived polyreactive antibodies and RF [30] and rearranged V H genes from PBL of a healthy donor [17]. For the J H segments we can confirm a predominant use of J H 4 [17,19].…”
Section: Discussionmentioning
confidence: 89%
“…In the rearrangement of the IgH gene, the usage of J H segments revealed a developmental stage-specific trend. [7][8][9][10][11][12][13] At the earliest stage of B cell development, the initial D-J H rearrangements predominantly occur between D H Q52 and J H -1 segments which are located close to each other. 53 During B cell development, a second or a third D-J H joining might occur, then the more 5ЈD segments and more 3ЈJ H segments would join at a later stage.…”
Section: Figurementioning
confidence: 99%
“…6 Studies on IgH variable region gene sequences at various stages of development have revealed stage-specific trends in the usage of V H , D, and J H segments, the degree of N nucleotide addition, and the rate of somatic mutations. [7][8][9][10][11][12][13] However, little is known of the organization and diversification of the IgL variable region gene on -chain. On the other hand, multiple myeloma (MM) has a variety of clinical features relating to clinical stage, prognosis and complication.…”
Section: Introductionmentioning
confidence: 99%
“…After alkaline denaturation and UV cross-linking of the DNA, the filters were hybridized with the CDR3-specific oligonucleotide probes and a JHC probe (Figure 1). 25 Pre-hybridization was performed in 6 × SSC (20 × SSC: 3 mol/l NaCl, 0.3 mol/l Na citrate, pH 7.0), 10 × Denhardt's (0.2% w/v Ficoll, 0.2% w/v polyvinyl pyrrolidone, 0.2% w/v BSA), 1% SDS and 100 g/ l boiled herring sperm DNA at 55°C. After prehybridization the denatured 32 P-labeled olignucleotide probes were added and the filters were hybridized at 55°C overnight.…”
Section: Hybridization To Pcr-amplified Cdna Librariesmentioning
confidence: 99%
“…The JHC probe consists of a mixture of four different oligonucleotides derived from the sequences of JH2, JH3, JH4 and JH6 genes. 25 To ensure that the JH4 olignucleotide also hybridized to JH1 and JH5 gene sequences, the hybridization was performed at 35°C and the filters were washed at lower stringency, ie 1 × SSC, 1% SDS at RT.…”
Section: Hybridization To Pcr-amplified Cdna Librariesmentioning
confidence: 99%